2020
DOI: 10.3892/mco.2020.2040
|View full text |Cite
|
Sign up to set email alerts
|

Miliary lung metastases from ROS1‑rearranged lung adenocarcinoma: A case report

Abstract: Miliary lung metastases are a rare form of metastasis of non-small-cell lung carcinoma. Miliary lung metastases commonly develop in lung adenocarcinoma with epidermal growth factor receptor mutation. In the present study, we present a case of miliary lung metastases from lung adenocarcinoma with ROS1 rearrangement. The patient, who had a history of surgery for stage IIIA lung adenocarcinoma, presented to our hospital with cough, dyspnea, and severe hypoxia. Chest computed tomography showed numerous tiny, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There are only few reports on the occurrence of MIPC in the existing literature. [5][6][7] MICP is characterized by uncountable discrete pulmonary micronodules, generally tiny and uniform in size (≤5 mm) and diffusely distributed throughout the lungs. 8,9 MICP may be predictive for rapid tumor progress.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few reports on the occurrence of MIPC in the existing literature. [5][6][7] MICP is characterized by uncountable discrete pulmonary micronodules, generally tiny and uniform in size (≤5 mm) and diffusely distributed throughout the lungs. 8,9 MICP may be predictive for rapid tumor progress.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging shows metastatic lymph-node tropism, often reported with less frequent extrathoracic metastatic sites than for ALK rearranged or epidermal growth factor receptor (EGFR)-mutated NSCLCs [ 28 ]. Miliary forms of lung metastases have also been described [ 29 ]. Several authors reported a heightened thromboembolic risk of ROS-1-rearranged tumors compared with NSCLCs harboring non-rearranged ROS-1 [ 30 ], and even rarer cases of thrombotic microangiopathies [ 31 ] and disseminated intravascular coagulation [ 32 ].…”
Section: Epidemiology Clinical and Histological Characteristicsmentioning
confidence: 99%